AdminForge: Declarative Privileged-Identity Management for Linux Server Fleets - Ribeiro, Rui de Quadros; Kapelinski, Cristhian; Kreutz, Diego (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
Stolen credentials are a leading cause of security breaches, yet on Linux server fleets the accounts, SSH keys, and permissions behind them are still often managed by hand. Centralized tools (Teleport, Boundary, FreeIPA) add a network-facing service that itself must be protected, and configuration-management tools have no notion of granting and revoking access. We present AdminForge, an open-source command-line tool that manages accounts, keys, and permissions from one operator machine: the operator edits the declared state, previews the changes, and applies them over SSH, recording every action in a local history and installing nothing on the hosts. Five professional Linux administrators completed its nine-task workflow without training, rating usefulness, ease of use and intention to use at a median of 6/7. A parallel apply, verify or audit over 50 hosts finishes in tens of seconds, and an unchanged re-apply answers locally in under 0.3 s, faster than an Ansible re-run and with no listening service added.